The universe in you : a microscopic journey - Chin, Jason, 1978- (Holiday House, 2022)
Explores life on the micro scale, from the smallest bird to human cells, molecules, and atoms, all the way down to particles too minuscule for humans to visualize. Includes back matter and additional resources.